2022
DOI: 10.1038/s41433-022-02217-w
|View full text |Cite
|
Sign up to set email alerts
|

A multi-centre prospective evaluation of THEIA™ to detect diabetic retinopathy (DR) and diabetic macular oedema (DMO) in the New Zealand screening program

Abstract: Purpose To validate the potential application of THEIA™ as clinical decision making assistant in a national screening program. Methods A total of 900 patients were recruited from either an urban large eye hospital, or a semi-rural optometrist led screening provider, as they were attending their appointment as part of New Zealand Diabetic Eye Screening Programme. The de-identified images were independently graded by three senior specialists, and final resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Previously we have demonstrated that it is possible to train an artificial intelligence (AI) deep learning (DL) algorithm on retinal images to grade diabetic retinopathy and maculopathy for diagnostic, screening and risk assessment purposes [30,[36][37][38][39][40][41][42][43][44][45]. In this study we used 110,272 fundus images from a database of 55,118 patients from the UK Biobank and AREDS 1 datasets to train and subsequently test a novel AI platform (CVD-AI) to calculate a 10-year CVD risk score for these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we have demonstrated that it is possible to train an artificial intelligence (AI) deep learning (DL) algorithm on retinal images to grade diabetic retinopathy and maculopathy for diagnostic, screening and risk assessment purposes [30,[36][37][38][39][40][41][42][43][44][45]. In this study we used 110,272 fundus images from a database of 55,118 patients from the UK Biobank and AREDS 1 datasets to train and subsequently test a novel AI platform (CVD-AI) to calculate a 10-year CVD risk score for these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The retinopathy, maculopathy, drusen, pigmentary abnormality, advanced age-related macular degeneration, and smoking CNNs were previously trained on other datasets. 16 , 22 , 23 The rest of the CNNs were trained using the unique UK Biobank labels in the fundus images: “hba1c_result,” “tchdl_result,” “systolic_bp,” “systolic_bp2,” “smoking_status.” “Systolic_bp” and “systolic_bp2” are 2 consecutive blood pressure measurements in the UK Biobank and in this study we used the mean of the two.…”
Section: Methodsmentioning
confidence: 99%
“…This model was built upon our previous work on detecting and grading retinopathy, maculopathy, macular degeneration, and effects of smoking in retinal images. 16 , 17 , 18 Although the Framingham risk score is recommended to perform cardiovascular risk assessment in some countries, 19 the 2018 American Heart Association (AHA) Cholesterol Clinical Practice Guidelines recommend using the US-derived PCE to estimate the 10-year risk for hard ASCVD events (coronary heart disease death, nonfatal myocardial infarction, fatal or nonfatal stroke). 15 Our DL model was trained on and validated against the 10-year ASCVD risk as calculated by the PCE from individuals in the UK Biobank dataset (Level 3 in Figure 1 ; Supplemental Appendix 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…175,788 fundus images from 85,707 individuals were obtained from the UK Biobank. A DL image screening system similar to the one used in our previous study [ 28 ] was created to screen for poor-quality images. In brief, a random set of images were first sampled from the UK Biobank dataset.…”
Section: Methodsmentioning
confidence: 99%